Biomechanics : circulation - Fung, Y. C. (Springer Science+Business Media, B.V., 1997)
The theory of blood circulation is one of the oldest in science, and remains a vigorous field of study with many features that have been described in physical and mathematical terms. In Biomechanics: Circulation, Fung presents a treatment of the fundamental biomechanics of the cardiovascular and pulmonary systems, using a mathematical approach to illuminate problems in experiemental design, data collection, modeling, observations, and theory. This second edition includes extensive changes incorporating major advances in hemodynamics that have occurred during the past decade. There are new chapters on coronary blood flow and skeletal muscle microcirculation. As in the first edition, Biomechanics: Circulation emphasizes the coupling of fluids and solids in the cardiovascular pulmonary systems, and consistently brings both morphology and rheology to bear on the analysis of blood flow. Numerous exercises are proposed to encourage the reader to formulate and solve problems. Together with his other two treatises on biomechanics (Biomechanics: Mechanical Properties of Living Tissue and Biomechanics: Motion, Flow, Stress and Growth), this book confirms that "although it is clear that Fung has made substantial contributions as a researcher ... it can equally well be said that he is an exceptional teacher" (Quart. Rev. Biol.). Y.C. Fung is professor emeritus in the Department of Bioengineering at the University of California at San Diego.